2011
DOI: 10.1002/adfm.201101570
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetic Cobalt Nanoparticles and Their Immobilization on Monomolecular Films and Chemical Templates

Abstract: Monodisperse Co nanoparticles (NPs), stabilized by organic coating have been synthesized, and their immobilization on a variety of self-assembled monolayers (SAMs) bearing different terminal groups and on SAM-based chemical templates has been studied. The NPs had an average diameter of ∼ 10 nm and consisted of hcp cobalt covered by a thin ( ∼ 1 nm) oxide fi lm.They exhibited pronounced ferromagnetic properties with a blocking temperature above 380 K, which is unusual for the given NP size and is presumably rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 93 publications
(143 reference statements)
0
14
0
Order By: Relevance
“…[56][57][58][59][60][61][62][63][64] As primary SAMs we mostly used those of the chemically inert, non-substituted alkanethiols on Au(111), with a preference for the dodecanethiolate (DDT) monolayer. [56][57][58][59][60][61][62][63][64] The basic experiments were performed with the primary SAM of either DDT or hexadecanethiolate (HDT) and mercaptoundecanoic acid (MUDA) or mercaptohexadecanoic acid (MHDA) as the substituents. [56,57] As the latter molecules carry carboxyl groups (COOH), their presence and concentration can be determined by X-ray photoelectron spectroscopy (XPS) and X-ray absorption spectroscopy (XAS).…”
Section: Basic Idea and Features Of Ipermentioning
confidence: 99%
See 2 more Smart Citations
“…[56][57][58][59][60][61][62][63][64] As primary SAMs we mostly used those of the chemically inert, non-substituted alkanethiols on Au(111), with a preference for the dodecanethiolate (DDT) monolayer. [56][57][58][59][60][61][62][63][64] The basic experiments were performed with the primary SAM of either DDT or hexadecanethiolate (HDT) and mercaptoundecanoic acid (MUDA) or mercaptohexadecanoic acid (MHDA) as the substituents. [56,57] As the latter molecules carry carboxyl groups (COOH), their presence and concentration can be determined by X-ray photoelectron spectroscopy (XPS) and X-ray absorption spectroscopy (XAS).…”
Section: Basic Idea and Features Of Ipermentioning
confidence: 99%
“…The molecules shown in Figure 3 were tested for IPER, with the outcome of this procedure monitored preferably by WCA goniometry and XPS, in combination with some other complementary techniques. [56][57][58][59][60][61][62][63][64] In nearly all cases, IPER worked quite well, with the ultimate extent of the promoted exchange depending on the specific combination of the primary SAM and the substituent. Interestingly, to a certain extent IPER could also be applied to aromatic SAMs, as was demonstrated using the biphenylthiolate/MUDA combination.…”
Section: Binary Sams Prepared By Ipermentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, oleylamine acted as a solvent, reducing agent, and surfactant [43,44], while oleic acid also aided as a surfactant. Oleic acid was introduced into the synthesis to enhance the shape control as it has been shown that oleic acid has a particularly strong affinity for cobalt in many cobalt-based NP syntheses [7,[45][46][47][48][49]. Oleic acid has also been found to improve the effectiveness of oleylamine [49] and their synergistic effect was expected based on the slight temperature increase of their solution upon simple mixing of the two surfactants.…”
Section: Ptco 3 Nanoparticle Synthesismentioning
confidence: 99%
“…For instance, ferrimagnetic NPs will lead to next generation of high density magnetic storage media and magnetite NP films will find applications in spintronics . Surface functionalization by layer‐by‐layer, self‐assembled monolayers, Langmuir–Blodgett, or dip‐coating deposition were used to assemble NP platforms whose stability was recently improved by covalent reticulation . However, these techniques are still difficult to implement in electronic or photonic nanodevices, due to structural defects and high sensitivity to chemical and electromagnetic environment .…”
mentioning
confidence: 99%